(untitled) (African Journal of Biomedical Research, 2022)
Introduction Prostate cancer is one of the leading causes of cancer mortality in Nigerian males. Multiple cytokines play a role in the aetiopathogenesis of prostate cancer. Interleukin – 2 (IL-2) and – 6 (IL-6) have been identified in the evolution of prostate cancer with possible therapeutic applications. The goal of this study was to investigate the serum levels of these cytokines in Nigerian males with prostate cancer. Materials and Methods This was a longitudinal study of 40 serially recruited patients with prostate cancer and 40 age- and sex matched-controls. Blood sample was taken from participants after obtaining informed consent. The samples were processed and analysed for prostate specific antigen (PSA), free PSA, IL-2, and IL-6. Results Plasma levels of IL-2 and IL-6 were significantly elevated in individuals with prostate cancer and directly correlated with plasma PSA and free PSA. The PSA and free PSA levels were also significantly higher in the study group than the control group. The %free PSA was < 25% in all study individuals with malignant prostate cancer and most patients had advanced disease with a Gleason score of 7-9. Conclusion The high plasma level of IL-2 in individuals with prostate cancer found in this study suggests active immune response; however, the failure to suppress malignancy may be due to activity modulation in the tumour microenvironment. Observed increase in IL-6 may contribute to disease progression by its direct androgenic action to prostate cancer cells. Hence, the prevalence of advanced disease in this study population may be the result of impaired IL-2 antitumour action and increased IL-6 activity.